2020
DOI: 10.7759/cureus.11154
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Non-Simultaneous Contralateral Second Hip Fractures: A Single-Center Irish Study

Abstract: Introduction Hip fractures are a significant cause of morbidity and mortality in the elderly and are also associated with increased healthcare costs. A second contralateral hip fracture can lead to even more complications and healthcare costs. A significant proportion of the Irish hip fracture population does not receive a bone health assessment or falls specialist assessment to reduce the risk of future falls and fractures. This study aimed to analyze the incidence of a non-simultaneous contralater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, other studies have challenged these findings. For example, Patrick Nolan et al [ 20 ] found that patients presenting with a second hip fracture were mostly female. Gaumetou et al [ 21 ] also showed that first and second hip fractures were predominantly in women.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have challenged these findings. For example, Patrick Nolan et al [ 20 ] found that patients presenting with a second hip fracture were mostly female. Gaumetou et al [ 21 ] also showed that first and second hip fractures were predominantly in women.…”
Section: Discussionmentioning
confidence: 99%
“…To be more precise, in the United States, a patient experiencing a proximal femoral fracture incurs approximately USD 40,000 in direct treatment costs and nearly USD 5000 for subsequent rehabilitation in the forthcoming years [6,7]. It is also worth mentioning that the average age of patients experiencing their initial proximal femoral fracture is 78.5 years, and that the mean duration until the occurrence of a second fracture is 37.2 months [8]. Furthermore, the first-year mortality rate increases by 21.2% in patients after their first hip fracture [9]; however, after their second hip fracture, this percentage is escalated to 55% [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who suffer a low-energy hip fracture are at imminent risk of future fragility fractures, including a second hip fracture [4,5]. Ten percent of patients hospitalized for a hip fracture will suffer a second hip fracture [4,5], with the highest risk of subsequent fracture within the first year [6][7][8]. There is strong evidence that initiation of anti-osteoporosis medication following hip fractures can significantly lower the risk of subsequent fractures [9] and may be associated with overall reduced mortality [10].…”
Section: Introductionmentioning
confidence: 99%